ANALISIS UNDERPRICING SAHAM DI BURSA EFEK INDONESIA PERIODE 2012-2017 - Linda Defi Ariyani; Hadi Ismanto (Jurnal Dinamika Ekonomi & Bisnis, 2019)
The phenomenon of underpricing of IPOs of companies on the still occurs due to economic uncertainty and a large information asymmetry. As many as 31 companies offered their shares to the primary market and underpricing. This study aims to provide empirical evidence regarding the factors that determine the underpricing of IPO shares on the from 2012 to 2017, including company size, auditor reputation, financial leverage, and EPS. This research uses a quantitative approach using 84 companies. The results of multiple linear regression indicate that stock underpricing is influenced by company size and auditor reputation, whereas Financial leverage and EPS do not lead to underpricing of IPO shares. Investors can consider the company's size and auditor's reputation as a benchmark for valuing IPO shares. This study also provides evidence that underpricing of IPOs can illustrate investor behavior in valuing developing companies.